Estimation Error in Income Determination. - Albrecht, William Steve (The Accounting Review, 1976)
Abstract This article focuses on the problem of estimation error in income determination. The author aims to provide a framework within which the uncertainty of the income statement can be computed and interpreted and then to illustrate, using a case study, the degree of uncertainty and resulting imprecision that does exist in one firm's earning computation. In accounting, two variables, suggestively, are of considerable interest: first, the flow of earnings over a specified period, and second, the stock of wealth at the end of that period. Based on the study, it is concluded that forecasting error can arise from two sources. There can be forecasting error about the amount of an item, such as, salvage value of fixed assets or the amount of uncollectible accounts; or there can be forecasting error about the timing of an item, such as, service lives of fixed assets. Another source of uncertainty in financial statements results from measurement or counting errors. Hence, an artificial partitioning of the entity's life to obtain intermediate progress data regarding enterprise goal accomplishment is needed. The quantification of uncertainty in a period's earnings computation is a two-step process. The first step involves assessing the estimation error inherent in each of the determinants of net income; the second step involves aggregating the uncertainty variables to find the cumulative effect for the period.